Analisis Kebutuhan Lahan Parkir Minimarket di Kecamatan Garut Kota - Gaitsah, Siti Yasmin Ghalilah (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
The growth of minimarkets has greatly influenced transportation in Garut Kota District. The lack of parking provided by several minimarkets has resulted in parking on the road which will result in traffic jams. The aim of this research is to determine the characteristics of parking and obtain a needs model so that the parking area required in a minimarket can be calculated.Data collection was carried out by survey counting vehicles directly affected by the minimarket. The vehicle towing results were analyzed using Linear Regression Analysis to obtain a good equation model. The research results showed that the need for minimarket parking space obtained from the analysis results was Y?? = 0.518 + 0.412 x (R=0.929), Y?? = 0.073 + 0.74 x (R=0.920), Y?? = 0.244 + 0.353 x (R=0.978) with x = Modern Shop Area. From the resulting model, it can be seen that the area required for minimarket parking space at 15 minute intervals is 40.25 m²/100 m² of shop area